STREAMLINING PRESCRIPTION TRANSFERS IN U.S. PHARMACIES: CHALLENGES AND INNOVATIVE SOLUTIONS - Venkata Siva Prasad Maddala (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive article explores the challenges and innovative solutions in prescription transfer systems within U.S. pharmacies, focusing on the transformation from traditional methods to modern digital platforms. The article examines the current infrastructure, technical bottlenecks, and emerging solutions while highlighting the integration of artificial intelligence, blockchain technology, and electronic prescription transfer systems. The article investigates the implementation strategies, security frameworks, and operational efficiencies across various healthcare facilities, demonstrating significant improvements in processing times, error reduction, and patient satisfaction through technological adoption. The article also addresses the critical aspects of staff training, resource allocation, and change management methodologies essential for successful system modernization in healthcare environments.